1998
DOI: 10.1177/104345429801500306
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in Children and Adolescents With Cancer

Abstract: Fatigue is a common symptom found in the adult oncology literature. However, little is known about its occurrence, causes, conceptual and operational definitions, and effective interventions in children and adolescents with cancer.The purpose of this study was to define and describe fatigue experienced by children and adolescents receiving treatment for cancer. A focus group approach was used to reveal the contextual understanding of fatigue through discussions. Eleven focus groups were convened during a 2-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
115
0
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(132 citation statements)
references
References 19 publications
9
115
0
8
Order By: Relevance
“…[44] One study solely used focus groups, [46] and one used diaries only [36]. One study used focus groups with the adolescent subsample participating in semi-structured interviews [18] and one study used questionnaire interview sheets [40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[44] One study solely used focus groups, [46] and one used diaries only [36]. One study used focus groups with the adolescent subsample participating in semi-structured interviews [18] and one study used questionnaire interview sheets [40].…”
Section: Resultsmentioning
confidence: 99%
“…Fatigue has physical, mental, and emotional components and may be characterized by a lack of energy, decreased physical ability, and feelings of tiredness. [16][17][18] Fatigue is a subjective, multidimensional construct [3] that may occur acutely, episodically, or chronically [3,17,19] with multifactorial etiology [3,20].…”
Section: Introductionmentioning
confidence: 99%
“…24 -26 In pediatric cancer, the measurement of fatigue is exemplified by the work of HockenberryEaton, Hinds, and colleagues. 8,27 In the development of the PedsQL Multidimensional Fatigue Scale, multidimensional constructs were derived from reviews of both the adult and pediatric cancer fatigue literature and integrated into the PedsQL Measurement Model.…”
mentioning
confidence: 99%
“…As a cancer related symptom, fatigue has often been focused in a number of studies from a variety of perspectives and several scales have been consequently developed to identify the symptom in detail and adapted into different languages (Cleeland et al, 2000;Radbruch et al, 2003;Wang et al, 2004;Lin et al, 2006;Shun et al, 2006;Wu et al, 2006). Neverthless, it is worth noting that the studies on fatigue in pediatric populations still remain insufficient and based on one group (Hinds et al, 1999a(Hinds et al, : 1999bHinds and Hockenberry, 2001;Hockenberry et al, 1998Hockenberry et al, : 1999.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore concluded that both subjective and objective evaluation would provide the most precise data in the assessment of fatigue as a perception based symptom in children and adolescents. An analysis of the pediatric oncology literature illustrated that the cancer related fatigue has been evaluated not only by children with cancer but also by their parents and staffs (Hockenberry et al, 1998(Hockenberry et al, : 2003Hinds et al, 1999b;Hinds & Hockenberry-Eaton 2001;Braud et al, 2003;Gibson et al, 2005Gibson et al, : 2006Ekti and Conk, 2008;Yeh et al, 2008;Perdikaris et al, 2009). Children and their parents may be adversely influenced when the symptoms can't be managed effectively during the long and painstaking cancer treatment which may lead to disintegrity and dysfunctionality in the family, the deterioriation of the quality of life, loss of energy, and increasing care burden and despair (Woodgate and Degner, 2004).…”
Section: Introductionmentioning
confidence: 99%